Analysis of the United Nations - African Union Hybrid Peace Support Operations in Darfur - Heywood, Limpho A; Maeresera, Sadiki (Adonis and Abbey Publishers Ltd, 2021)
This chapter focuses on the African Union-United Nations Hybrid Operation in Darfur (UNAMID), a peacekeeping mission created by the UN Security Council in July 2007 to protect civilians in Sudan in the wake of the Darfur crisis, monitor ceasefire agreements, and support the implementation of the Darfur Peace Agreement signed in May 2006. After providing an overview of the conflict in Darfur, the chapter outlines UNAMID’s mandate and evaluates its operational achievements and limitations, particularly in terms of providing protection to civilians and internally displaced persons. It argues that UNAMID’s record was mixed, with its principal failures stemming from a lack of resources, its inability to overcome Khartoum’s obstructionism, and its flawed strategic vision.